Book Review: Fragrant Frontier: Global Spice Entanglements from the Sino-Vietnamese Uplands - Thompson, C. Michele (Agricultural History, 2024)
The editors of Fragrant Frontier have produced an impressively researched book on the contemporary growers, in northern Vietnam and Southwest China, of three spices—star anise, black cardamom, and cinnamon, each of which has local, regional, and international economic importance—as well as the human links in the global commodity chain of these spices. This volume is much more coherent than many edited volumes, and readers should not skip any of it, as there are nice little surprises waiting here and there in the text.A good example is the “Preface and Acknowledgements” section, as this not only provides interesting information on how the volume came into being but also links to websites and scannable QR codes for “story maps” on the three spices and the places mentioned in the rest of the volume. This is a nice touch that gives this volume about the recent situation of farmers, local traders, marketplace workers, street vendors (of both the spices and foods prepared with them), wholesalers, exporters, and state officials a very contemporary feel. These story maps are only the first of an extensive number of relevant, well-done, and well-used illustrations including photographs, maps, and tables inserted throughout the following chapters.
Keywords: book.review; dept.his

Book Review: Epidemic Politics in Contemporary Vietnam: Public Health and the State By Martha Lincoln, London: Bloomsbury Academic. 2022. 232 pp.1 - Thompson, C. Michele (Medical Anthropology Quarterly, 2024)
Keywords: book.review; dept.his